2015
DOI: 10.1128/genomea.01290-15
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Citrobacter sp. CtB7.12, Isolated from the Gut of the Desert Subterranean Termite Heterotermes aureus

Abstract: The draft genome of Citrobacter sp. CtB7.12, isolated from termite gut, is presented here. This organism has been reported as a cellulolytic bacterium, which is biotechnologically important because it can be used as a gene donor for the ethanol and biofuel industries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Citrobacter has been commonly reported to form associations with a wide variety of insects, including R. ferrugineus (Muhammad et al, 2017; Tagliavia et al, 2014), pine weevils (Hernández‐García et al, 2017), termites (Fontes‐Perez et al, 2015; Upadhyaya et al, 2012), and flies (Cheng et al, 2017). Its occurrence in the intestinal microbiota of insects of differing orders suggests a generalized role in diet supplementation (Meng et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Citrobacter has been commonly reported to form associations with a wide variety of insects, including R. ferrugineus (Muhammad et al, 2017; Tagliavia et al, 2014), pine weevils (Hernández‐García et al, 2017), termites (Fontes‐Perez et al, 2015; Upadhyaya et al, 2012), and flies (Cheng et al, 2017). Its occurrence in the intestinal microbiota of insects of differing orders suggests a generalized role in diet supplementation (Meng et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Besides the Treponema endosymbionts, several extracellular bacteria previously isolated from termite guts have been shown to have urease enzyme activity, such as Comamonas odontotermitis [71]; or encode operons for urease and their transporters in their genomes including a Citrobacter strain [72], Sporomusa termitida [73], Stenoxybacter acetivorans [74], and several Verrucomicrobia strains [75][76][77][78][79]. Yet, owing to their low abundance relative to the total prokaryotic community and the fact that we did not detect any of these taxa at proportions greater than 0.5% in our ureC gene dataset suggests that ureolysis in the gut lumen by freeswimming bacteria likely does not produce a significant quantity of recycled N for Reticulitermes termites.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of Citrobacter in the gut flora of insects of different orders may suggest its general role in supplementing their diets. Indeed, previous studies have reported that different members of Citrobacter are associated with nitrogen fixation, uric acid recycling, and cellulose degradation in the guts of different insects (Additional file 1: Appendix C) [12, 4448]. In addition, different members of Citrobacter from soils are commonly associated with other processes of nitrogen metabolism, e.g.…”
Section: Discussionmentioning
confidence: 99%